Sanksi Hukum terhadap Pejabat Negara yang Melanggar Protokol Kesehatan di Masa Pandemi Covid-19 - I Kadek Arya Andika; I Nyoman Sugiartha; I Nyoman Sutama (Jurnal Interpretasi Hukum, 2021)
The corona virus or what is known as Covid-19 is an infectious disease caused by a new type of coronavirus that was discovered at the end of 2019 in the city of Wuhan, China, which has spread throughout the world, has killed hundreds of people and infected tens of thousands of others. Previously, Indonesia was one of the countries that had not been infected, and finally in February the corona virus entered Indonesia. The spread of the corona virus causes panic among Indonesian people. The purpose of this study is to uncover legal sanctions against state officials who violate health protocols during the COVID-19 pandemic. The research method used is a normative legal research method where the reference is based on a conceptual approach to legislation. Sources of materials and laws used are primary and secondary. The data collection technique used is to collect references related to research. Furthermore, the data will be processed and analyzed using legal data processing methods systematically. The results of this study indicate that cases of spread and death rates caused by the corona virus are now increasing quite rapidly, a number of countries have even taken action by prohibiting every citizen from traveling abroad or receiving visits from foreign nationals (lockdown). In order to deal with the unrest experienced by the Indonesian people and efforts to prevent the transmission of the corona virus which is increasingly increasing the number of positive patients, the government issued several regulations or policies, namely Government Regulation of the Republic of Indonesia Number 21 of 2020, concerning Large-Scale Social Restrictions. (PSBB) in the context of accelerating the handling of the 2019 coronavirus disease (covid-19).